การพัฒนากลยุทธ์การบริการสารสนเทศของสำนักหอสมุดแห่งชาติ - ลำงาม, วิภานันท์; วรัญญานุไกร, สมชาย; แสนวา, ศุมรรษตรา (บรรณศาสตร์ มศว, 2018)
การวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาสภาพปัญหาและความต้องการของผู้ใช้บริการสำนักหอสมุดแห่งชาติ วิเคราะห์สภาพแวดล้อมภายในและภายนอกในการบริการ และพัฒนากลยุทธ์การบริการสารสนเทศของสำนักหอสมุดแห่งชาติ โดยใช้วิธีวิจัยเชิงคุณภาพ เครื่องมือที่ใช้ในการวิจัย คือ แบบสัมภาษณ์ และการสนทนากลุ่ม ผู้ให้ข้อมูลหลัก คือ ประชาชนผู้เข้ามาใช้บริการสำนักหอสมุดแห่งชาติ จำนวน 20 คน และผู้ให้บริการสำนักหอสมุดแห่งชาติ จำนวน 15 คน โดยใช้วิธีคัดเลือกแบบเจาะจงผลการวิจัยดังนี้ 1. ปัญหาของผู้ใช้บริการ คือ ทรัพยากรสารสนเทศมีไม่เพียงพอ ไม่ทันสมัย ชำรุด เจ้าหน้าที่ขาดจิตบริการ และแต่งกายไม่เหมาะสม ไม่มีมุมอาหารว่างและเครื่องดื่ม จุดบริการเชื่อมต่อโน้ตบุ๊กมีไม่เพียงพอ และห้องน้ำไม่สะอาด สามารถสืบค้นผ่านเว็บไซต์ไม่ได้ ส่วนความต้องการของผู้ใช้บริการ คือ ทรัพยากรสารสนเทศที่หลากหลาย เจ้าหน้าที่มีจิตบริการและแต่งกายเรียบร้อย มีมุมอาหารว่างและน้ำดื่ม จุดบริการเชื่อมต่อโน้ตบุ๊ก ความสะอาดของห้องน้ำ มุมบริการสารสนเทศพิเศษ และสืบค้นผ่านเว็บไซต์ ได้สะดวก 2. การวิเคราะห์สภาพแวดล้อมภายในและภายนอกในการบริการสารสนเทศพบว่า 1) จุดแข็ง คือ ทรัพยากรสารสนเทศหลากหลาย มีบริการพิเศษ ไม่เสียค่าใช้จ่ายในการใช้บริการ และการคมนาคมสะดวก 2) จุดอ่อน คือ การเข้าถึงข้อมูลไม่สะดวก การประชาสัมพันธ์ไม่ทั่วถึง ขาดสิ่งอำนวยความสะดวก ผู้ให้บริการขาดความเชี่ยวชาญเฉพาะด้าน กฎระเบียบในการเข้าใช้บริการไม่เหมาะสม 3) โอกาส คือ การได้รับงบประมาณพิเศษ การได้รับหนังสือตามพระราชบัญญัติจดแจ้งการพิมพ์ พ.ศ. 2550 เครือข่ายความร่วมมือกับหน่วยงานภายนอกและ 4) อุปสรรคคือ งบประมาณไม่เพียงพอต่อการพัฒนางานของสำนักหอสมุดแห่งชาติ 3. กลยุทธ์การบริการสารสนเทศของสำนักหอสมุดแห่งชาติ ได้แก่ การพัฒนาให้เป็นคลังทรัพยากรสารสนเทศของชาติเพื่อการให้บริการ การพัฒนาเครือข่ายความร่วมมือด้านทรัพยากรสารสนเทศกับหน่วยงานภายนอก การพัฒนาสมรรถนะ ความรู้ และทักษะด้านการบริการแก่บุคลากร การพัฒนาพื้นที่การทำงานและพื้นที่ในการเรียนรู้ การให้บริการเทคโนโลยีสิ่งอำนวยความสะดวกสำหรับผู้พิการ การพัฒนาเทคโนโลยีสารสนเทศที่ทันสมัย การพัฒนาสื่อสังคมออนไลน์ในการให้บริการตอบคำถามและช่วยการค้นคว้า การพัฒนาทรัพยากรสารสนเทศดิจิทัล และการให้บริการเบ็ดเสร็จ ณ จุดเดียว This research aims to study the problems and the needs of users at the National Library of Thailand through an analysis of the internal and external environment in the National Library and developed an information service strategy at the National Library through qualitative research. The methods used in the study were interviews and group discussions. The twenty key informants were the users who came to the National Library and fifteen staff members. The results are as follows: 1. The problems of the users - the information resources are insufficient, out of date, cannot be found or damaged, some of the staff lacked service mindedness and dressed in improper outfits, lacked a snacks and drinks corner, not enough notebook connection points and the restrooms were not clean, users are unable to access online catalogues and the problem of searching information resources in the database. The needs of the users - the wide range of information resources are required, the staff has a service minded and dressed in a proper outfit, provide a snacks and drinks corner and also a laptop connection point, an improvement in the cleanliness of the restrooms, provided a special resources service corner, to be able to search the National Library website and database. 2. An analysis of the internal and external environment found the following 1) strengths - the wide range of information resources, the special services, users can also access the service free of charge; 2) weaknesses - inaccessibility to information, lack of public relations and facilities, service providers lack the expertise, the access rules were not consistent with current library service trends; 3) opportunities - the allocation of special budgets, regarding the acquisition under the Registration Act of 2007, government support for staff attending local; 4) obstacles - inadequate budgets to improve and develop the work of the National Library. 3. The information services strategy of the National Library are as follows: the development of the national information resource and to enhance library networking on library resources with external organizations to complement the services provided, the development of service capabilities for personnel, the development of working and learning spaces and the development of technology services for the disabled, the development of social media in answering the demands of research services, the development of digital information resources and the development of integrated single point service.